Energi Panas Bumi: Sumber Daya yang Dibentuk oleh Struktur Geologi - Citra Wahyu Ningrum; Edo Stanzah; Assyeh Annasrul Majid (Ocean Engineering : Jurnal Ilmu Teknik dan Teknologi Maritim, 2023)
Geothermal energy is a renewable energy source that can be used to generate electricity, heat homes and businesses, and provide hot water for industrial processes. The interior of the Earth is hot, and this heat can be transferred to the surface through geological structures such as faults, fractures and sedimentary basins. These structures provide pathways for geothermal fluids to flow, and they can also trap these fluids, creating geothermal reservoirs. The type and size of geological structures that affect geothermal energy can vary depending on the location. For example, in some areas, faults and fractures are the most important structures, while in other areas, sedimentary basins are the most important. The distribution of these structures also plays a role in determining the potential for developing geothermal energy. The study of geological structure is very important to understand the distribution and potential of geothermal energy resources. By understanding how these structures influence the circulation and accumulation of geothermal fluids, we can develop and better manage these resources. This abstract provides a brief overview of the topic of geothermal energy and the role of geological structures in this field. It is intended to provide a starting point for further research and discussion.